2022
DOI: 10.1021/acscatal.2c04527
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Computational Design of Single-Atom/Cluster Catalysts for Electrochemical and Solar-Driven N2 Fixation

Abstract: Fixation of dinitrogen into ammonia is an essential biological process for the evolution of life, and at the same time ammonia is an essential component for many industrial processes, including fertilizers, plastics, and so on. NH 3 is also known as the best alternative to H 2 in fuel cells. However, due to chemical inertness, direct conversion of N 2 into NH 3 is not possible; a suitable catalyst is required. The century-old Haber−Bosch process, utilizing an Fe-based catalyst, is extremely energy-intensive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 246 publications
0
27
0
Order By: Relevance
“…However, Kuznetsov et al reported experimentally that the Gibbs free energy in HER for the MXene phase of Mo 2 CT x can be substantially decreased and approach zero by the synthesis of a solid solution of the Mo 2 CT x :Co MXene phase with cobalt substitution on the molybdenum sites and without a post-synthetic modification of the parent MXene. Similarly, the S or Te atom can also be added to the PtTe 2 or Sb 2 S 3 monolayer and form a solid solution of PtTe 2 :S or Sb 2 S 3 :Te to reduce the Gibbs free energy . It indicates that the present PtTe 2 /Sb 2 S 3 heterostructure with a normalΔ G normalH * of 1.145–1.396 eV can also drive HER feasibly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Kuznetsov et al reported experimentally that the Gibbs free energy in HER for the MXene phase of Mo 2 CT x can be substantially decreased and approach zero by the synthesis of a solid solution of the Mo 2 CT x :Co MXene phase with cobalt substitution on the molybdenum sites and without a post-synthetic modification of the parent MXene. Similarly, the S or Te atom can also be added to the PtTe 2 or Sb 2 S 3 monolayer and form a solid solution of PtTe 2 :S or Sb 2 S 3 :Te to reduce the Gibbs free energy . It indicates that the present PtTe 2 /Sb 2 S 3 heterostructure with a normalΔ G normalH * of 1.145–1.396 eV can also drive HER feasibly.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the S or Te atom can also be added to the PtTe 2 or Sb 2 S 3 monolayer and form a solid solution of PtTe 2 :S or Sb 2 S 3 :Te to reduce the Gibbs free energy. 63 It indicates that the present PtTe 2 /Sb 2 S 3 heterostructure with a G H * of 1.145−1.396 eV can also drive HER feasibly.…”
Section: Carrier Mobility and Optical Absorptionsmentioning
confidence: 99%
“…In addition, to further verify the thermodynamical stability of the AE-SAC systems, the energy difference (Δ E b ) between E b and E coh was calculated. 64 In which, E coh is the cohesive energy of AE metal bulk and can be calculated using the formula of E coh = ( E bulk – nE AE )/ n , where E bulk is the total energy of the AE metal crystal and n is the number of metal atoms in the crystal. A negative Δ E b indicates that the AE metal single atom tends to remain isolated on the substrate rather than agglomerate, and a more negative Δ E b means higher thermodynamical stability.…”
Section: Methodsmentioning
confidence: 99%
“…17,18 Until now single and double atom catalysts (SACs and DACs) of different transition metals with variable supports have been screened efficiently both experimentally and theoretically, leading to various design principles and important generalizations for catalyst design with respect to the NRR. 19–42 Along similar directions, there has been a greater demand to design transition metal free catalysts (TMFCs) for the NRR due to their promising catalytic activity and durability. In addition, the cheap and abundant nature of TMFCs makes their development for N 2 reduction highly imperative from an economic point of view.…”
Section: Introductionmentioning
confidence: 99%